Metal-THINGS: Association and optical characterization of supernova remnants with H I holes in NGC 6946 - Lara López, M. A. (2023)
Context. NGC 6946, also known as the-Fireworks Galaxy, is an unusual galaxy that hosts a total of 225 supernova remnant (SNR) candidates, including 147 optically identified with high [SII]/Hα line ratios. In addition, this galaxy shows prominent HI holes, which have been analyzed in previous studies. Indeed, the connection between SNRs and HI holes along with their physical implications in the surrounding gas are worthy of attention. Aims. This paper explores the connection between the SNRs and the HI holes, including an analysis of their physical link to observational optical properties inside and around the rims of the holes, using new integral field unit (IFU) data from the Metal-THINGS survey. Methods. We present an analysis combining previously identified HI holes, SNR candidates, and new integral field unit (IFU) data from Metal-THINGS of the spiral galaxy NGC 6946. We analyzed the distributions of the oxygen abundance, star formation rate surface density, extinction, ionization, and diffuse ionized gas, as well as the Baldwin-Phillips-Terlevich classification throughout the galaxy. Results. By analyzing the optical properties of the 121 previously identify HI holes in NGC 6946 in detail, we find that the SNRs are concentrated at the rims of the HI holes. Furthermore, our IFU data show that the star formation rate and extinction are enhanced at the rims of the holes. To a lesser degree, the oxygen abundance and ionization parameter show hints of enhancement on the rims of the holes. Altogether, this provides evidence of induced star formation taking place at the rims of the holes, whose origin can be explained by the expansion of superbubbles created by multiple supernova explosions in large stellar clusters dozens of Myr ago.